Creation of shared value in cooperatives: Informal institutions' perspective of small-sized banana growers from Colombia - Marcela Maestre Matos; Jahir Lombana; Francisco J. Mesías (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This study aims to identify informal institutions for bottom-of-the-pyramid (BoP) business models in the agricultural sector through the case study of banana growers' cooperatives. Design/methodology/approach - A case study of six banana cooperatives from Colombia was conducted. The research followed a mixed design, using both qualitative and quantitative data and the application of structural equations. Findings - This study shows that social capital, networking and alliances are essential in BoP businesses. Originality/value - Authors defined a model of informal institutional factors for the generation of economic and social value in inclusive business, using the new institutional theory and the conceptual development of BoP in agri-business.
Keywords: J54; M14; O17; Q13; 330; Shared value; Informal institutions; Bottom of the pyramid